In Defense of the Lecture: Revisiting and Reassessing Its Place within Management Pedagogy. (2nd October 2019) - Offstein, Evan H.; Chory, Rebecca M.
ABSTRACT: Long the staple or go-to technique in management education, instruction via the lecture has fallen on hard times. Dismissed as professorially heavy-handed and lacking creativity, the lecture has yielded considerable ground to experiential, service, applied, and active learning techniques. In this essay, we question this shift away from the lecture toward the aforementioned trending instructional methods. In coming to the defense of the lecture, we explore the benefits afforded by the lecture for students and the professorate. Drawing on the maxim that what is old is new again, we contend that the lecture still deserves central billing in the management student experience. To do so not only enhances the occupational prestige of the faculty, but also enhances student learning and prepares students for career success in the professional management world. To close, we explore how the lecture format can best be preserved in management education and the modifications needed to realize its many benefits.